Transcranial magnetic stimulation for the treatment of chronic low back pain: a narrative review - Olechowski, Camille; Gener, Maricar; Aiyer, Rohit; Mischel, Nicholas (Frontiers in Pain Research, 2023)
Background: Chronic low back pain is a debilitating condition that impacts mil-lions of individuals around the world, and also has an enormous economic impact. Consequently, it is critical to approach these patients with multimodal management. However, many patients experience refractory low back pain to these initial treatments, which can result in non-resolving chronic pain. As a result, many new interventions have been developed in recent years to treat refractory low back pain, including non-invasive transcranial magnetic stimulation. Our objective is to provide a narrative review of the treatment of chronic low back pain with transcranial magnetic stimulation. Methods: We performed a comprehensive database search on PubMed, Embase, PsychInfo, Web of Science, and CINAHL using these terms: “Chronic Low Back Pain and Transcranial Magnetic Stimulation”, “Low Back Pain and Transcranial Magnetic Stimulation”, “Chronic Back Pain and Transcranial Magnetic Stimulation”, “Chronic Low Back Pain and TMS”, “Low Back Pain and TMS”, and “Chronic Back Pain and TMS”. Results: Search results from September to November 2021 using the above mentioned search criteria included 458 articles, filtered based on various exclusion and inclusion criteria. The resulting 6 studies are discussed. Discussion: The studies reviewed suggest the potential benefit in chronic lower back pain symptoms after various rTMS protocols and sites of stimulation. However, the included studies are not randomized, not blinded or have small sample size. This review highlights the need for better controlled large scaled research studies and standardization.